ROC analízis alkalmazása - Fazekasné Kis, Mária (Acta Agraria Debreceniensis, 2002)
According to publishings in foreign scientific journals, ROC (Receiver Operating Characteristic) analysis is a widely used method for analysing the diagnostic utility of clinical laboratory tests. In this paper, we explain the basic principles of ROC analysis and produce ROC curves, as well as demonstrate some ROC curves, which represent the results of diagnostic tests.